2011
DOI: 10.1007/s13361-010-0032-5
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Protein-Fatty Acid Interactions Using Electrospray Ionization Mass Spectrometry

Abstract: The application of the direct electrospray ionization mass spectrometry (ESI-MS) assay to quantify interactions between bovine β-lactoglobulin (Lg) and a series of fatty acids (FA), CH 3 (CH 2 ) x COOH, where x=6 (caprylic acid, CpA), 8 (capric acid, CA), 10 (lauric acid, LA), 12 (myristic acid, MA), 14 (palmitic acid, PA) and 16 (stearic acid, SA), is described. Control ESI-MS binding measurements performed on the Lg-PA interaction revealed that both the protonated and deprotonated gas phase ions of the (Lg +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
104
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(126 citation statements)
references
References 26 publications
9
104
1
1
Order By: Relevance
“…Furthermore, different instruments sometimes produce divergent results for the same interaction. However, over the past decade, a number of methodological advances have significantly improved the reliability and applicability of the ESI-MS assay, and affinities measured for a multitude protein-ligand complexes, as well as other types of biological complexes have been shown to be in agreement with values determined by other analytical methods [14][15][16][17][18][19][20][21][22][23]. So, does this mean that the ESI-MS assay has matured to the point where the technique can be reliably used by researchers who do not have extensive training in MS?…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…Furthermore, different instruments sometimes produce divergent results for the same interaction. However, over the past decade, a number of methodological advances have significantly improved the reliability and applicability of the ESI-MS assay, and affinities measured for a multitude protein-ligand complexes, as well as other types of biological complexes have been shown to be in agreement with values determined by other analytical methods [14][15][16][17][18][19][20][21][22][23]. So, does this mean that the ESI-MS assay has matured to the point where the technique can be reliably used by researchers who do not have extensive training in MS?…”
Section: Introductionmentioning
confidence: 95%
“…However, it is important to note that the gas-phase stabilities of PL complexes generally do not parallel the solution binding affinities. For example, some PL complexes, which are stabilized by strong ionic interactions in solution, exhibit low gas phase stabilities [47], while some PL complexes formed by hydrophobic bonding are quite stable in the gas phase [23,50,51]. Collisional heating of gaseous ions may occur at various stages during the ion sampling process, such as within the heated metal sampling capillary (if used), in the nozzle (or orifice)-skimmer region, and during accumulation of ions within external rf multipole storage devices (e.g., hexapole) [14,36,47,50,51].…”
Section: In-source Dissociationmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of SF-1, its affinity for a range of different phospholipids was explored by treating the protein with liposomes of different constitution and monitoring the abundance of the resulting adducts by ESI mass spectrometry [7]. More recently, Klassen and coworkers demonstrated that stable complexes between bovine β-lactoglobulin and different fatty acids could be formed by nano-electrospray ionization [49]. In this study, in-source dissociation of the delicate complexes was minimized by the addition of a high concentration of imidazole to the electrospray solution.…”
Section: Mass Spectrometry For Direct Interrogation Of Lipid-protein mentioning
confidence: 99%